Grain yield and interspecific competition in an oat-common vetch intercropping system at varying sowing density - Wang, Ying; Han, Xue; Zhao, Xingyao; Zhang, Yanli; Qi, Bingjie; Li, Lijun (Frontiers in Plant Science, 2024)
Oat (Avena nuda L.) and common vetch (Vicia sativa L.) intercropping has resulted in substantial production capabilities. However, there is currently a dearth of research on whether this intercropping system can enhance productivity through increased seeding rates. A two-year field experiment was conducted to investigate the yield, biological efficiency, economic efficiency, and competition indicators of oats and common vetch in a high-density intercropping system. Two cropping patterns (monocropping and intercropping) and five seeding rates (D1: 4.5×106 plants hm-2; D2:5.4×106 plants hm-2; D3:6.3×106 plants hm-2; D4: 7.2×106 plants hm-2; and D5: 8.1×106 plants hm-2) were arranged in a randomized block design. The intercropped oats exhibited greater grain yield than the monocultures. Increasing the oat seeding rate significantly enhanced oat yield, with the D3 level in intercropping showing the highest yield increase. The land equivalent ratio was maximized at the D2 level in both years and was significantly higher than D1, with biological indicators suggesting that increasing oat seeding rates improved the productivity of the intercropping system, with the best performance observed at the D2 level. For both years, the proportionate actual yield loss of oat was the highest at the D3 level; significantly surpassing D1, proportionate actual yield loss of common vetch and actual yield loss were the highest at level D2, both significantly surpassing D1. With an increased oat seeding rate, the economic benefits of the intercropping system were maximized at the D2 and D3 levels. Regarding intercropping competition, oat was the dominant crop under different seeding rates (Aggressivity for oat (AO)>0, relative crowding coefficient for oat (KO)>1, competition ratio for oat (CRO)>1), whereas common vetch was the inferior crop. Compared with the D1 level, the D2 level significantly increasing crowding coefficient for common vetch (KV) and competition ratio for common vetch by 19.76% to 21.94% and 4.80% to 7.51%, respectively, while reducing KO and CRO. This result suggests that in the intercropping of common vetch and oat in alpine regions, rational densification can harmonize interspecific competition and thus improve the biological efficiency and economic benefits of intercropping systems.